ANALISA VARIASI BAHAN BAKAR RON 92 JENIS PERTAMAX SHELL SUPER DAN AKRA92 PADA PERFORMA DAN KONSUMSI BAHAN BAKAR MOTOR 4-LANGKAH HONDA BEAT FI 110cc TAHUN 2013 - Dedy Rachman Ardian; Mokhammad Faris Kurniawan (Wahana Teknik, 2022)
The performance of motorized vehicles that are more than five years old tends to decline. Today, fuel manufacturers are very diverse, even though they have the same octane rating. Each fuel certainly has different characteristics. The need for testing to determine the performance and consumption of the motor. This study aims to determine the effect of Pertamax, Shell Super, AKRA92 fuel with 92 octane on performance and efficiency, especially on automatic motorcycles Honda Beat FI 110cc in 2013. Fuel. From the dynotest results, the torque and power produced by the AKRA92 are 13.15Nm and 12.72HP, then Pertamax 11.51Nm and 11.91HP, the last is Shell Super 10Nm and 11.72HP. Meanwhile, from the test results of fuel consumption efficiency per 250 ml, namely AKRA 92 10.37km then Pertamax 9.95km and lastly Shell Super 9.64km. Of the three fuels, the most efficient in fuel consumption is AKRA92. Fuel that has high performance will automatically have a more complete combustion. If the resulting combustion is complete, the energy produced will be greater with the same amount of fuel. This is what causes the fuel that has high performance automatically fuel consumption will be low.